Lie Point Symmetries and Travelling Wave Solutions for the Generalized Drinfeld–Sokolov System. Issue 4 (6th June 2016) - Garrido, T. M.; Bruzón, M. S.
ABSTRACT: In this article, we show successful methods with a wider applicability in physics, which have been applied to make an analysis of generalized Drinfeld–Sokolov system. Lie's classical symmetries have been calculated and they have given us the Lie-group classification depending on the parameters. Moreover, for each case we have obtained their optimal system and reductions to conclude obtaining traveling wave solutions using the sine–cosine method.